3D scaffolds in breast cancer research. (March 2016) - Rijal, Girdhari; Li, Weimin
Abstract: Breast tumors grow in a tissue microenvironment containing extracellular matrix (ECM), adipocytes, stromal cells, fluids, and blood vessels. This natural yet complex physiopathological territory is dynamically remodeled in favor of tumor growth and metastasis. The environment-mimicking 3D cultures have shown compelling advantages in the studies of tumor cell biology, and are of intensive research for the development of alternative systems to improve therapeutic efficacies against tumors. This review focuses on the most recent advances in scaffolding techniques, the cell-ECM and cell-cell interactions in scaffold cultures, the distinct physical properties and signaling regulation of cancer cell growth within the scaffolds, the sensitivities of the cancer cells to drugs in 3D culture, and the use of scaffolds for drug delivery into tumors.